Importance of head movements in gaze tracking during table tennis forehand stroke - Shinkai, R.; Ando, S.; Nonaka, Y.; Yoshimura, Y.; Kizuka, T.; Ono, S. (bioRxiv, 2023)
The purpose of this study was to clarify the properties of gaze and head movements during forehand stroke in table tennis. Collegiate table tennis players (n = 12) conducted forehand strokes toward a ball launched by a skilled experimenter. A total of ten trials were conducted for the experimental task. Horizontal and vertical movements of the ball, gaze, head and eye were analyzed from the image recorded by an eye tracking device. The results showed that participants did not always keep their gaze and head position on the ball throughout the entire ball path. Our results indicate that table tennis players tend to gaze at the ball in the initial ball-tracking phase. Furthermore, there was a significant negative correlation between eye and head position especially in the vertical direction. This result suggests that horizontal VOR is relatively suppressed than vertical VOR in ball-tracking during table tennis forehand stroke. Finally, multiple regression analysis showed that the contribution of head position to gaze position was significantly higher than that of eye position. This result indicates that gaze position during forehand stroke could be associated with head position rather than eye position. Taken together, head movements may play an important role in maintaining the ball in a constant egocentric direction in table tennis forehand stroke.